Nutrient uptake, grain and stover yield of pearl millet (Pennsisetum glaucum L.) at different levels of mineral fertilizer and foliage of Jatropha curcas L. - Abdullahi Aliyu, Nuraddeen; Ismail, Roslan; Mohammad Yusoff, Martini; Mohd Anuar, Mohd Firdaus; K/Naisa, Adamu Garba (International Journal of Modern Agriculture, 2020)
Foliage of JatrophacurcasL. as soil amendment to improve pearl millet productivity was evaluated under field conditions at Kadawa (11.650°N & 8.450°E) Nigeria. The treatments consisted of 3 rates of jatropha foliage (0, 5t/ha and 10t/ha) and 3 rates of mineral fertilizer (0, half and full recommended rates of N-P-K. 60:30:30. Kg/ha). Experimental design was the randomized complete block with three replications. Using standard procedures, the soil and jatropha foliage were characterized for nutrient elements content, while the uptake of nutrients (N.P.K) was calculated by multiplying nutrient concentration (%) and the corresponding yield (kg/ha). Results showed that the native soil was of low fertility status and the foliage was a suitable organic amendment that can be incorporated in to soil. Mineral fertilizer alone or in combination with the foliage significantly increased both grain and stover yields, while jatropha foliage alone did not achieve optimum yield levels. Also, nutrients uptake was significantly higher in plotstreated with mineral fertilizer alone or in combination with foliage of jatropha. Generally, the complementary use of half recommended rate of mineral fertilizer and 10t/ha rate of jatropha foliage was always at par with the full recommended rate of mineral fertilizer in terms of yields and nutrients uptake. This suggests that farmers can establish jatropha plants around their fields to use the foliage along with lower rates of mineral fertilizer for enhanced pearl millet productivity.